The Role of Strategic Management Accounting In The Development of Sustainable Development Goals (SDGs) In The Field of Decent Work To Support The Economic Growth of Ntt Province - Yanuar Ramadhan; Rio Bernando Sirait; Achmad Chusanudin; Erna Longa; Dewi Kurniawati (Journal Research of Social Science, Economics, and Management, 2022)
Work is very important in the context of human well-being. Besides providing income, jobs also pave the way to broader economic and social improvements. This study used the Systematic Literature Review method. This research was conducted by collecting research data in the form of documentation in the form of research journals and other data. This research has the results, namely that it should be in realizing the goals of sustainable development goals (sdgs) in the field of decent work to support the economic growth of East Nusa Tenggara Province, the need for Tourism-based development supported by infrastructure development and the synergy of community elements, so that a system will be created that can realize people get decent jobs and improve the economy of East Nusa Tenggara Province